Knockout of MITOGEN-ACTIVATED PROTEIN KINASE 3 causes barley root resistance against Fusarium graminearum - Basheer, Jasim; Vadovič, Pavol; Šamajová, Olga; Melicher, Pavol; Komis, George; Křenek, Pavel; Králová, Michaela; Pechan, Tibor; Ovečka, Miroslav; Takáč, Tomáš; Šamaj, Jozef (Plant physiology, 2022)
The roles of mitogen-activated protein kinases (MAPKs) in plant-fungal pathogenic interactions are poorly understood in crops. Here, microscopic, phenotypic, proteomic, and biochemical analyses revealed that roots of independent transcription activator-like effector nuclease (TALEN)-based knockout lines of barley (Hordeum vulgare L.) MAPK 3 (HvMPK3 KO) were resistant against Fusarium graminearum infection. When co-cultured with roots of the HvMPK3 KO lines, F. graminearum hyphae were excluded to the extracellular space, the growth pattern of extracellular hyphae was considerably deregulated, mycelia development was less efficient, and number of appressoria-like structures and their penetration potential were substantially reduced. Intracellular penetration of hyphae was preceded by the massive production of reactive oxygen species (ROS) in attacked cells of the wild-type (WT), but ROS production was mitigated in the HvMPK3 KO lines. Suppression of ROS production in these lines coincided with elevated abundance of catalase (CAT) and ascorbate peroxidase (APX). Moreover, differential proteomic analysis revealed downregulation of several defense-related proteins in WT, and the upregulation of pathogenesis-related protein 1 (PR-1) and cysteine proteases in HvMPK3 KO lines. Proteins involved in suberin formation, such as peroxidases, lipid transfer proteins (LTPs), and the GDSL esterase/lipase (containing "GDSL" aminosequence motif) were differentially regulated in HvMPK3 KO lines after F. graminearum inoculation. Consistent with proteomic analysis, microscopic observations showed enhanced suberin accumulation in roots of HvMPK3 KO lines, most likely contributing to the arrested infection by F. graminearum. These results suggest that TALEN-based knockout of HvMPK3 leads to barley root resistance against Fusarium root rot.
Keywords: Proteomics; Transcription Activator-Like Effector Nucleases; Fusarium; TALENs; reaktivní formy kyslíku; ječmen (rod); mitogenem aktivovaná proteinkinasa 3; Hordeum; Mitogen-Activated Protein Kinase 3; nemoci rostlin; proteomika; Reactive Oxygen Species; Plant Diseases